Examining the influence of information system ratings on the performance of 3PL companies. Issue 3 (2017) - Joo, Seong-Jong; Yun, Gawon
This study examines the influence of information system ratings on the performance of third-party logistics (3PL) companies using two DEA models along with one-way analysis of variance. The findings of this study are twofold: first, there is no significant performance difference at a group level by the information system ratings, which has been confirmed with analysis of variance; second, however, we have confirmed performance differences at an individual or company level due to the information system ratings using data envelopment analysis (DEA). The major contribution of this study is the first attempt to measure 3PL performance in conjunction with information systems that help supply chain management with tracking and locating products and sharing information among supply chain players.